The child support in the Peruvian law: A vision from the law and economics - Baldino Mayer, Nicolás (2020)
This article is part of the Child support law of descendants and it focuses on two objectives: first, to establish a minimum and maximum amount that serves to satisfy the basic needs of those supported, and second, to determine whether there are adequate regulatory incentives to promote the compliance of the maintenanceobligation and responsible procreation. In this way, using concepts and tools of the economic analysis of the law, we will study both the behaviour of the obligated parent and the importance that the norm acquires as a vehicle of information for family planning, all this concerning for the number of children and the income necessary for responsible parenthood. In this regard, the regulation can improve information on the cost of a child so that individuals can make better decisions.